Empowering Girls in India - SINGH, DILBAAG (THE PRIMARY TEACHER, 2015)
If you educate a man you educate an individual, however, if you educate a woman you educate a whole family. ‘Woman empowered means Mother India empowered’ has rightly been said by Pt. Jawaharlal Nehru on the eve of Independence. We are now living in a democratic country and all the citizens, male or female, in such a country have the right of equality according to constitutional provisions. The same is also applicable in concerning the education of a girl. Today in India there are many Schemes and Acts in practice which are for the all-around development of girls. Education is the major issue. All Acts and schemes are useless if the beneficiary is not literate and not able to know. Only an educated girl can fight for her rights. Before making so many other schemes and providing facilities, we have to make sure that the girls, for whom schemes/programmes are made, can access the existing provisions. It is possible and easier for a well aware and educated girl to access her rights. Education should be a priority for girls. Recently Central Government as well State Governments have introduced many schemes for the improvement of girl’s education. Some of them are: ‘Dhanlakshmi scheme’, ‘Bhagyalakshmi scheme’, ‘Ladli scheme’, ‘Rajlakshmi scheme’, ‘Rakshak scheme’ etc. After RTE Act, 2009 a positive attitude has been noticed in the Indian society, particularly in Rural areas regarding girls education. The role of media and information technology cannot be ignored in this regard to promote and popularise the expanded outlook of people. It is the right of a child (girl or boy) to get education. Between the age group of 6 and 14 years the elementary education is completely free for each child. There are also some special schemes for the single girl child. For the girls in higher education, there are some other schemes too. In this paper the focus is on how girls can be empowered by education and to analyse the role and impact of RTE to enhance girls education after the execution of Children’s Right to Free and Compulsory Education Act, 2009. This paper also analyses the impact of various means for communication, Films, Television and Information Technology to enhance the empowerment of Girls through Education in India in post-RTE era.